Concrete setting in cold joints and its impact on the flexural strength of structural beams (Gaceta Técnica, 2026)
This study examines the impact of concrete setting time in cold joints on the flexural strength of structural beams. The methodology employed was a hypothetical-deductive scientific method, using an explanatory and correlational approach. A quasi-experimental design was used with concrete beams distributed into a control group and four experimental groups, for a total of 45 samples, under a 2² factorial design. The results revealed that controlled interruptions of up to 30 minutes during setting significantly improve structural strength, while prolonged interruptions of up to 60 minutes deteriorate the bond and reduce strength. Furthermore, the type of joint and the duration of the interruption were determining factors in the concrete's behavior. These findings highlight the need for rigorous control of joint timing and types in construction to optimize the durability and safety of structures, providing valuable technical criteria for sustainable civil engineering
Keywords: concrete setting; structural strength; flexural strength; cold joints